Sophocarpine Suppresses NF-κB-Mediated Inflammation Both In Vitro and In Vivo and Inhibits Diabetic Cardiomyopathy - Zou, Fang; Wang, Ling; Liu, Han; Wang, Wei; Hu, Longlong; Xiong, Xiaoying; Wu, Lijuan; Shen, Yunfeng; Yang, Renqiang (Frontiers in Pharmacology, 2019)
Diabetic cardiomyopathy (DCM) is a leading cause of mortality in patients with diabetes. Diabetic cardiomyopathy (DCM) is a leading cause of mortality in patients with diabetes. We used both in vitro and in vivo experiments to investigate the hypothesis that sophocarpine (SPC), a natural quinolizidine alkaloid derived from a Chinese herb, could protect against DCM. We used hyperglycemic myocardial cells and a streptozotocin (STZ)-induced type 1 diabetes mellitus mouse model. SPC protected myocardial cells from hyperglycemia-induced injury by improving mitochondrial function, suppressing inflammation, and inhibiting cardiac apoptosis. The SPC treatment significantly inhibited the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling in high-glucose-stimulated inflammatory responses. Moreover, SPC significantly slowed the development and progression of DCM in STZ-induced diabetic mice. These results show that SPC suppresses NF-κB-mediated inflammation both in vitro and in vivo and may be used to treat DCM.